European Commissioner cabinet advisers: Policy managers, bodyguards, stakeholder mobilizers. (9th February 2017) - Gouglas, Athanassios; Brans, Marleen; Jaspers, Sylke
Abstract : The article investigates the substantive and dimensional aspect of advisers' policy work in the cabinets of European Commissioners. Advisers' roles are mapped using Connaughton's (2010a) typology of four adviser types and Maley's (2015) framework of three arenas. Using data collected via a survey and follow‐up face‐to‐face interviews with European Commissioner cabinet advisers in the Juncker Commission in 2015, it is shown that the majority of those agents perform policy coordination and political bodyguard functions. They are both policy managers who steer policy and political bodyguards who mind the Commissioner. It is also their core work responsibility to be highly active across three arenas: orientate and mobilize officials in the Directorate Generals, coordinate policy across Commissioner cabinets, and build political support through consulting and bargaining with external stakeholders. European Commissioner cabinet advisers are individual agents active within a variant of the ministerial cabinet system tradition.